Longitudinal Study of Maternal Beliefs About Infant Crying During the Postpartum Period: Interplay With Infant’s Temperament - Hiraoka, Daiki; Nomura, Michio; Kato, Masaharu (Frontiers in Psychology, 2021)
Infant crying is an important signal for their survival and development, and maternal beliefs about crying predict responsiveness to crying. Most studies have considered caregivers’ reactions to crying to be fixed, and it is unclear how they change with their caregiving experience. Additionally, it has recently been suggested that there is a bidirectional relationship between changes in mothers’ beliefs about crying and infants’ temperament. This study examined that relationship using a longitudinal study design. Maternal beliefs about crying and infant temperament of 339 Asian first-time mothers (mean age = 28.7 years, SD = 4.1) were measured at 1-month intervals over 4 months. There were 289 participants in Wave 2, 240 in Wave 3, and 164 in Wave 4. Prior to the main survey, we conducted a pre-survey to confirm the reliability and validity of the Japanese version of the Infant Crying Questionnaire. We found that parent-oriented beliefs, which focus on the caregiver rather than the crying infant, increased with the mother’s experience. The results showed that parent-oriented beliefs, which focus on the caregiver rather than the crying infant, increased in mothers who had infants aged three months or older at Wave 1. We also found that the process of change in maternal beliefs was not uniform, and that infants high on surgency predicted changes in maternal beliefs about infant crying. Longitudinal studies of caregivers’ changes, such as the present study, are expected to contribute to understanding the co-development of caregivers and infants.